Cross-cultural intersemiotic translation of commercials —analysis of Dolce & Gabbana's controversial advertisement - Zhang, Le (Nanyang Technological University, 2023)
Globalization is an inevitable trend for brands who wish to win the oversea market. Cross-cultural advertisement is one of the main ways to achieve the globalization goal. This study examines the failure of cross-cultural advertisement which insulted and lost its target market from an intersemiotic translation perspective. It provides solutions to avoid the failure being copied by other brands. Applying Peirce’s triadic model, the paper analyzes cultural elements in D&G’s commercial advertisement including close-ups, color, characters and props. Attention should be paid to getting rid of cultural bias and stereotypes in an international marketing environment. Keywords: intersemiotic translation, semiotics, Peirce’s triadic model, cross-cultural commercial, audio-visual advertisement